2012
DOI: 10.1016/j.bbamcr.2012.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive intestinal peptide (VIP) inhibits human renal cell carcinoma proliferation

Abstract: Clear renal cell carcinoma (cRCC) is an aggressive and fatal neoplasm. The present work was undertaken to investigate the antiproliferative potential of vasoactive intestinal peptide (VIP) exposure on non-tumoral (HK2) and tumoral (A498, cRCC) human proximal tubular epithelial cell lines. Reverse transcription and semiquantitative PCR was used at the VIP mRNA level whereas enzyme immunoanalysis was performed at the protein level. Both renal cell lines expressed VIP as well as VIP/pituitary adenylate cyclase-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…It is reported that in A172 and U87MG human glioblastoma cells, PKA and EPAC1 pathways synergistically promote cAMP-induced cell death and cell cycle arrest [34], while in clear renal cell carcinoma (cRCC) A498 cells, growth-inhibitory response to vasoactive intestinal peptide (VIP) is shown to be mediated by EPAC/PI3K pathway [35]. In contrast, EPAC1 promotes cell proliferation and survival by up-regulating Ras/MAPK and PI3K/AKT/mTOR signaling in prostate cancer cells [36,37].…”
Section: Epac1 In Cancer Cell Proliferation and Apoptosismentioning
confidence: 99%
“…It is reported that in A172 and U87MG human glioblastoma cells, PKA and EPAC1 pathways synergistically promote cAMP-induced cell death and cell cycle arrest [34], while in clear renal cell carcinoma (cRCC) A498 cells, growth-inhibitory response to vasoactive intestinal peptide (VIP) is shown to be mediated by EPAC/PI3K pathway [35]. In contrast, EPAC1 promotes cell proliferation and survival by up-regulating Ras/MAPK and PI3K/AKT/mTOR signaling in prostate cancer cells [36,37].…”
Section: Epac1 In Cancer Cell Proliferation and Apoptosismentioning
confidence: 99%
“…There are several data indicating nephroprotective effects of PACAP against different toxic agents , such as oxidative stress (Horvath et al 2010a, kidney ischemia (Szakaly et al 2008;Horvath et al 2010b), diabetes (Banki et al 2013(Banki et al , 2014, myeloma- (Arimura et al 2006a, b;Li et al 2007), gentamicin- (Li et al 2008), cisplatin-(Li et al 2011, and cyclosporine A-induced nephropathy ), but we have only few data about its effect in kidney tumors. Recently, Vacas et al (2012) demonstrated that VIP and VPAC1 receptors are expressed in tumoral human proximal tubular epithelial cell line and VIP is able to prevent tumor progression. PACAP shows very close similarity to VIP, therefore, we suggest that it could have a potential role in the development of kidney tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Hence local inhibition of peptidergic system in papillary type RCC may partly be responsible from resistance to immunotherapy. Furthermore NEP-induce hydrolysis of VIP creates selective VPAC-1 receptor agonist which has anti-proliferative and antiinflammatory effects [36]. Hence loss of NEP activity may prevent anti-tumoral effects of VIP on RCC.…”
Section: Discussionmentioning
confidence: 99%